Implementación de un sistema de gestión ambiental en función de los factores ambientales en hospitales - Gallegos-Pasco, Pedro (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a study presented to the National University of the Altiplano, which aimed to implement an environmental management system to manage Water, Air and Soil resources, develop environmental review, and identify Environmental Management programs at Manuel Núñez Butrón Hospital in Puno (Peru). In addition to defining all the elements of the International standard: Environmental Policy, identification of environmental aspects, highlighting hospital solid waste, identification of legal requirements, establishment of environmental objectives and goals, availability of resources, functions and responsibilities, authority, competence, training and awareness, communication, documentation, document control, operational control, emergency preparedness and response, monitoring and measurement, evaluation of legal compliance, non-conformities, corrective action and preventive action, control of records, internal audit and review by the address. The methodological process establishes the necessary elements for the design of an Environmental Management System, where the methodology established in the International Standard ISO 14001 is applied, with which it is expected to improve the quality of care, quality of service, health and environmental performance, by controlling the aspects and tasks that cause or could cause negative impacts to the Hospital environment. Identification and assessment of significant environmental aspects and impacts, the information was taken through average weight measurements, generation of Solid Waste. Finally, the Manual of the Environmental Management System for the Hospital was prepared to conduct its activities in a positive way towards the environment, patients and people in general. It also provides the necessary information for its implementation. The results indicate that the sterilization of solid waste reaches the conclusion; the analysis of variance (ANOVA), after sterilization, shows a calculated "F" value of 585.89, this being higher than the critical value of 1.85, showing that the means or averages are different and significant for the value of 0.000, the Pearson's R Correlation Test shows a value of 0.996 which indicates a direct and almost perfect relationship and the "t" test shows significant differences between the means whose reduction is 0.86083, on average by day, it is concluded that sterilization significantly improves the management of environmental factors in the operating room area of ​​said hospital.